Universal Criminal Jurisdiction - Issa, Hussein Abd Ali; Mahmood, Shirwan Ali (Journal of Legal and Political Studies, 2019)
The universal criminal jurisdiction, its definition, scope and application by the national judiciary has been occupied by many jurists, Even the General Assembly of the United Nations has participated in its efforts to define the principle, define its scope and urge its application, These ongoing efforts. This research sheds light on this principle and highlights its importance and role in combating the perpetrators of the most serious international crimes and pursuing them to prevent them from escaping punishment.
Keywords: criminal jurisdiction; General Assembly; United Nations; perpetrators; international crimes